PERSEPSI MASYARAKAT PESISIR UTARA KABUPATEN SIKKA TERHADAP FUNGSI MANGROVE SEBAGAI PENAHAN GELOMBANG TSUNAMI - Barnabas P. P. W. Bhokaleba; Erfin Erfin (Universitas Pattimura, 2022)
The North Coastal of Sikka Regency is one of the tsunami-prone areas in East Nusa Tenggara Province. Mangrove forest has one of the ecological functions which is as a tsunami barrier. The aimed of this study were to: (1) analyze the condition of the mangrove forest on the north coastal of Sikka Regency before and after the 1992 tsunami (2) analyze the perception of the northern coastal community of Sikka Regency on the function of mangroves as a buffer against tsunami waves. This research was survey research using primary data and secondary data. The research location located in Reroroja Village of Magepanda District, Sikka Regency. The research was conducted from February to July 2022 with the number of respondents being interviewed as many as 70 people. The results of the study revealed that the condition of the coastal area of Reroroja Village before the tsunami disaster was an arid vacant land and was used as land for farming. Conditions after the tsunami disaster, this area had overgrown with various mangrove vegetation and planting had been carried out since 1993 by a group of mangrove farmers. The benefits of mangroves for the community as a provider of wood, fish, crabs, and bees. In addition, as a tourism and learning place. Most coastal communities feel the impact of the tsunami disaster and consider the function of mangroves to be very important as a buffer against tsunami waves.